Development of solar powered notebook - Salmah, Mahful (2010)
The Notebook powered by it battery is convenience to use where AC outlet is not available such as in more rural and underdeveloped areas. However, Notebook can drain it battery with heavy use in just a few hours, leaving the user searching for power outlet. With development of Solar Powered Notebook, the sun is the electricity needed to keep the Notebook running for hours longer where Solar or Photovoltaic (PV) Cells are used to collect solar energy for direct use to power up the Notebook. The design of the circuit can be summarized into four distinct circuits that work in tandem to generate the desired output of 20V from a solar panel input. The first is Boost Converter circuit to take in the input voltage from the solar panel and step up the voltage to the desired 20V as required by the Notebook. The second is timer circuit where it utilized the LM555 timer, which drives the MOSFET that operates as the switch in the Switch-Mode Boost Converter topology. The third is Active PFC Feedback circuit, this circuit allows for regulation of the output voltage so that the Boost Converter is only on for as long as necessary to maintain a voltage of 20V. Finally, there is the Voltage Clipper Circuit, which is the actual output voltage to the Notebook. This project suitable for scientists or researchers who work far away from civilization and power outlet. The Solar Powered Notebook proved to be energy saving because free energy, environmental benefits which reduce CO2 emissions associated with global warming and it works where there is no grid available.